2008
DOI: 10.1016/j.vaccine.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Towards a human oral vaccine for anthrax: The utility of a Salmonella Typhi Ty21a-based prime-boost immunization strategy

Abstract: We previously demonstrated the ability of an orally administered attenuated Salmonella enterica serovar Typhimurium strain expressing the protective antigen (PA) of Bacillus anthracis to confer protection against lethal anthrax aerosol spore challenge [1]. To extend the utility of this approach to humans we constructed variants of S. enterica serovar Typhi Ty21a, an attenuated typhoid vaccine strain licensed for human use, which expressed and exported PA via two distinct plasmid-based transport systems: the Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
0
35
1
2
Order By: Relevance
“…Mice were boosted intramuscularly on day 42 with 10 g of recombinant PA83 (List Biological Laboratories, Campbell, CA) adsorbed to 0.5 mg of Alhydrogel and administered in a total volume of 50 l. Serum samples were collected at 0, 13, 41, 48, 55, and 70 days and stored at Ϫ70°C until analyzed. PA83-specific serum immunoglobulin G (IgG) and toxin neutralization activity (TNA) titers were measured in individual animals as previously described (1,12). All animal experiments and procedures were approved by the Institutional Animal Care and Use Committee of the University of Maryland Baltimore School of Medicine.…”
Section: Vol 78 2010 Ssb-stabilized Plasmids For Live Vectors 339mentioning
confidence: 99%
“…Mice were boosted intramuscularly on day 42 with 10 g of recombinant PA83 (List Biological Laboratories, Campbell, CA) adsorbed to 0.5 mg of Alhydrogel and administered in a total volume of 50 l. Serum samples were collected at 0, 13, 41, 48, 55, and 70 days and stored at Ϫ70°C until analyzed. PA83-specific serum immunoglobulin G (IgG) and toxin neutralization activity (TNA) titers were measured in individual animals as previously described (1,12). All animal experiments and procedures were approved by the Institutional Animal Care and Use Committee of the University of Maryland Baltimore School of Medicine.…”
Section: Vol 78 2010 Ssb-stabilized Plasmids For Live Vectors 339mentioning
confidence: 99%
“…77 Interestingly the proportion of toxin neutralizing to non-neutralizing PA specific antibodies that make up the response appears to vary depending on how the antigen is presented to the immune system. 78 It was also recently reported that while PA 20 , the N terminal domain of the protein, was recognized by 62% of monoclonal antibodies (Mabs) isolated from AVA immunized individuals only 18% of them demonstrated TNA in contrast to 44% of Mabs which bound to PA 63 . 79 This finding supports earlier studies that showed that domain 4 of PA, the region responsible for binding to host cell receptors and a major component of PA 63 , but not domain 1 (the major part of PA 20 ) is capable of mediating protection when delivered in the correct context.…”
Section: Mechanism Of Protectionmentioning
confidence: 94%
“…106 The feasibility of employing an orally delivered Salmonella strain to protect mice against a lethal aerosol anthrax spore challenge has been demonstrated, initially using Salmonella enterica serovar Typhimurium and subsequently with S. enterica serovar Typhi Ty21a, an attenuated typhoid vaccine strain licensed for use in humans. 78,81,107 While these results are promising they have yet to be extended to humans although a recent study in nonhuman primates demonstrated that a prime-boost immunization strategy in which animals nasally primed with S. typhi vaccine strain CVD 908-htrA expressing PA mounted robust PA specific immune responses when given a parenteral boost with either rPA or AVA. 108 The ability of prime-boost regimes to enhance protective immunity has been increasingly recognized and different successful prime-boost combinations have been reported for a number of vaccine candidates further supporting the use of Salmonella as a potential anthrax priming vaccine for humans.…”
Section: Third Generation Anthrax Vaccinesmentioning
confidence: 99%
“…This research has included analyses of PA polypeptide domains (Flick -Smith et al, 2002b ;Yan et al, 2008 ), DNA vaccines (Galloway and Baillie, 2004 ), alternative delivery technologies (Luxembourg et al, 2008 ;Mikszta et al, 2005 ), evaluation of novel adjuvants (Kelly et al, 2007 ;Kim et al, 2008 ;Park et al, 2008 ), oral and mucosal vaccines Baillie et al, 2008 ;Bielinska et al, 2007 ;Jiang et al, 2006 ;Stokes et al, 2007 ), and PA -producing liveattenuated vaccines (Ivins et al, 1990 ;Skoble et al, 2009 ).…”
Section: Anthrax Vaccine Researchmentioning
confidence: 99%
“…Baillie et al used Salmonella enterica serovar Typhi Ty21a to express and export a ClyA -PA fusion protein and demonstrated protective immuAnthrax Vaccine Research 283 nity after mucosal priming followed by a parenteral PA or AVA boost (Baillie et al, 2008 ). The fact that in mice a protein boost is still necessary illustrates the diffi culty in achieving consistent protection by nasal or oral vaccination alone.…”
Section: Vaccine Delivery Technologiesmentioning
confidence: 99%